Keanekaragaman Tanaman di Kebun Kelompok Wanita Tani (KWT) Madumulyo dalam Upaya Optimalisasi Penggunaan Lahan Perkotaan - Intan Dwi Kurniasari; Faiza Aliya Nur; Nabila Dila Septhia (Politeknik Negeri FakFak, 2024)
Over time, land use change has become more prevalent, which has resulted in the reduction of green open land, especially in urban areas. As a result, biodiversity is decreasing. In the face of this, KWT Madumulyo, as the Madumulyo Women Farmers Group RT 07/RW 01 Pulisen, Boyolali is considered capable of adapting to the current conditions, through its efforts in providing food and medicine sources for local residents. So that the purpose of this research is to be able to inventory plant species cultivated by the Madumulyo Women Farmers Group (KWT) in Kebun Lestari as an effort to optimize urban land use and improve the welfare of the Madumulyo RT 07 / RW 01 community through the provision of sustainable food and medicine sources. The method used in this research is descriptive analysis, where the interview process and literature study are then described. The results obtained show high plant diversity with various benefits, both as food and medicine. There are 47 species of plants that are cultivated, including categories of vegetables, flowers, fruits, spices, as well as plant parts that are utilized, such as leaves, rhizomes, tubers, stems, flowers, and seeds. The dominance of vegetable plants reached 42.55% of the total species, followed by fruit at 25.53%. To optimize land use and improve the welfare of the local community. To optimize land use and improve community welfare, these gardens also play a role in providing sustainable food and medicine sources, which can increase self-reliance and encourage more efficient and environmentally friendly use of natural resources.